Clinical pathway for the treatment of malocclusion in children with OSA - ZHAO Tingting, HE Hong (Editorial Office of Stomatology, 2024)
Obstructive sleep apnea(OSA)in children is the most serious type of sleep disordered breathing. If left untreated, it can lead to serious complications, including malocclusion, which in turn can lead to the occurrence and development of OSA. The treatment of malocclusion in OSA children requires multidisciplinary cooperation. It is recommended that orthodontists pay close attention to the sleep breathing condition of children with OSA. The orthodontists should comprehensively consider children's age, growth and development stage, severity of OSA and malocclusion manifestations, and formulate personalized treatment plans to create favorable conditions for the healthy development of the dentofacial and even the whole body of children.